Detection of a quasi-periodic oscillation in γ-ray light curve of the high-redshift blazar B2 1520+31. Issue 4 (11th February 2019) - Gupta, Alok C; Tripathi, Ashutosh; Wiita, Paul J; Kushwaha, Pankaj; Zhang, Zhongli; Bambi, Cosimo
ABSTRACT: We detected a possible quasi-periodic oscillation (QPO) of ∼71 d in the 0.1–300 GeV γ-ray Fermi -Large Area Telescope light curve of the high-redshift flat spectrum radio quasar B2 1520+31. We identify and confirm that quasi-period by Lomb–Scargle periodogram and weighted wavelet Z-transform analyses. Using this QPO period, and assuming it originates from accretion disc fluctuations at the innermost stable circular orbit, we estimate the central supermassive black hole mass to range between ∼5.4 × 10 9  M⊙ for a non-rotating black hole and ∼3.4 × 10 10  M⊙ for a maximally rotating black hole. We briefly discuss other possible radio-loud active galactic nuclei emission models capable of producing a γ-ray QPO of such a period in a blazar.